Reorganizacao do processo condilar da articulacao temporomandibular apos condilectomia unilateral, em camundongos tratados com zidovudina (AZT) - Balducci-Roslindo, E. [UNESP]; Roslindo, N. C. [UNESP]; Hetem, S. [UNESP]; Maruyama, N. T. [UNESP]; Vilarinho, S. [UNESP] (My University, 1996)
In order to analyze the reorganization of the condylar process after unilateral condylectomy in animals which have received AZT, 30 albino mice, 30 days old were used. The condylectomized animals were divided in two groups, one have received distilled water and the other AZT, orally during 10 days. After 5, 10, 15, 30 and 45 days of the surgery the animals of both groups were sacrificed, their heads removed and fixed in 10% formalin. After decalcification the pieces received histological routine treatment to be included in paraffin. The slices were stained by hematoxylin/eosin method. The analysis of results showed that: 1. the condylar repair is similar on both groups; 2. the results reaffirm those found in the literature, that the articulation after condylectomy is located in an anterior position and that the articular disc is not a determinant factor on condylar reorganization.
Reorganization of the condylar process of the temporomandibular joint after unilateral condylectomy in mice treated with zidovudine (AZT)
Keywords: mandibular condyle/surgery; mice; temporomandibular joint; zidovudine; animal experiment; histology; mandible resection; mouse; nonhuman; oral drug administration